Ensaios sobre segurança no trânsito - Lima, Robson Oliveira (2021)
Traffic accidents represent one of the largest causes of death in the world, with increase evidence that low and middle income countries are being disproportionately affected. Brazil has adopted policies aimed at reducing accidents and decrease its severity. In 2010, Programa Nacional de Controle de Velocidade, National Plan for Speed Control, was implemented with the objective of installing thousands of electronic speed cameras on Brazilian federal highways. Amidst several criticisms about the program’s effectiveness, it was briefly interrupted in 2019. Using data about traffic accidents for the period 2011-2018, we build a panel for thousands of roads that were treated by a speed camera. We took advantage of the staggered way as electronic cameras were being installed on federal roads to identify their effect on the total number of road accidents using a event study empirical strategy. Our results seem to suggest that the installation of a camera on a site can reduce accidents and its severity. When analysing heterogeneity in the relationship between site characterists and accidents rate, we conclude that speed cameras are more effective on rural sites and during daylight. Our second paper analyzed the role of decentralization of traffic accident policies had in reducing traffic accidents. In 1997, Brazil saw major changes to its Traffic Code, including a set of news responsibilities for its municipalities. Despite this changes, less than one third of Brazilian municipalities have adapted to the legislation. The coverage is not uniform, and some states have made a great effort to promote the universalization of the decentralization of transit policies in their territory. The state of Rio Grande do Sul has 95% its traffic controlled by local governments, so that we use its experience to evaluate the impact of descentralization on road safety. Again, we took advantage of the staggered adoption of policy and estimated that this policy had a small effect in reducing deaths, but was not able to reduce hospitalizations rate for traffic accidents. Local characteristics seem to play an important role in explaining the effects of this decentralization on accidents. Municipalities in the major metropolitan area seem to have taken more advantage of descentralization. An indication that traffic structure management have an important impact on accident reduction.